Peningkatan Hasil Belajar Siswa pada Materi Penjumlahan Pecahan Menggunakan Pendekatan Pendidikan Matematika Realistik (PMR) di Kelas IV SD N 11 Guguak VIII Koto Kabupaten Lima Puluh Kota - Risa Rahayu; Zuryanty Zuryanty (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research is behind the dilator by student learning outcomes that are not in accordance with what is expected. Thisy type of research is classroom action research using qualitative and quantitative approaches. The research was conducted in two cycles consisting of planning, implementation, observation, and reflection. Research data in the form of observations and actions and test results. The data source is the process and results of the implementation of student learning on fraction addition material using the Realistic Mathematics Education (PMR) approach. The research subjects were 26 teacher and grade IV students consisting of 19 men and 7 women.The results showed an increase in student learning outcomes in aspects of knowledge of the first cycle that is 81,% increased to 87.31% or increased about 6.16%. In the aspect of skills in Cycle I, namely 82.08% increased to 85.09% or an increase of about 3.01%. RPP observations results in the first cycle that is 83.92% increased to 92.85%. The observation of aspects of teachers and students in the first cycle that is 80% increased to 90%. It can be concluded that, the PMR approach can improve student learning outcomes in the fraction summation material using the Realistic Mathematics Education approach (PMR) in Class IV SDN 11 Guguak VIII Koto District Fifty Cities.